KERENTANAN DAN KETANGGUHAN ANAK JALANAN DI KOTA MAKASSAR DALAM MENGHADAPI PERMASALAHAN HIDUP SEHARI-HARI - Paskori, Andi Faisal; Putri Nabila, Dwi; Irsyad Syair, Muhammad; Galuh Gamayanti, Gatri; Daniel Bandaso, Teguh (JURNAL ILMU BUDAYA, 2023)
There have been many studies discussing street children in Makassar. However, research that looks at perspective of street children themselves, is something new, especially on the aspects of vulnerability and resilience. The objective of research is to analyze motive, vulnerability, and resilience of Makassar street children. This research is useful in providing new approaches in studying street children. By using cultural studies, research was analyzed with qualitative descriptive method with observation and interviews as data collection. This study discusses driving factors of street children, vulnerability and resilience that they face. From the discussion, it can be concluded economic factors are main factors. In addition, friends influence are also significant. Violence and bullying are often vulnerable things that afflict street children. However, they have ability to withstand pressure. By playing and tactics, street children are able to get fun and entertainment to get out of problems of life that hit them.